Tuber crops could be a potential food component for lowering starch digestibility and estimated glycemic index in rice - Kumar, Awadhesh; Mahapatra, Soumya; Nayak, Lopamudra; Biswal, Monalisha; Sahoo, Upasana; Lal, Milan Kumar; Nayak, Amaresh Kumar; Pati, Kalidas (Journal of the science of food and agriculture, 2024)
BACKGROUND Rice is considered a high estimated glycemic index (eGI) food because of its higher starch digestibility, which leads to type II diabetes and obesity as a result of a sedentary life style. Furthermore, the incresaing diabetes cases in rice‐consuming populations worldwide need alternative methods to reduce the glycemic impact of rice, with dietary prescriptions based on the eGI value of food being an attractive and practical concept. Rice is often paired with vegetables, pulses, tubers and roots, a staple food group in Africa, Latin America and Asia, which are rich in fibre and health‐promoting compounds. RESULTS Rice from four categories (high protein, scented, general and pigmented) was analyzed for eGI and resistant starch (RS) content. Among the genotypes, Improved Lalat had the lowest eGI (53.12) with a relatively higher RS content (2.17%), whereas Hue showed the lowest RS (0.19%) with the highest eGI (76.3) value. The addition of tuber crops to rice caused a significant lowering of eGI where the maximum beneficial effect was shown by elephant foot yam (49.37) followed by yam bean (53.07) and taro (54.43). CONCLUSION The present study suggests that combining rice with suitable tuber crops can significantly reduce its eGI value, potentially reducing the burden of diet‐associated lifestyle diseases particularly diabetics. © 2024 Society of Chemical Industry.